A New Tapped Inductor Buck Converter with Large Step-Down Voltage Conversion - Siripan Trakuldit; Chanin Bunlaksananusorn; Supat Kittiratsatcha (International Review of Electrical Engineering (IREE), 2023)
This paper presents a new DC(DC converter with large step-down voltage conversion. The proposed converter is obtained by cascading an input circuit of a Quadratic Buck Converter (QBC) to a Tapped Inductor Buck Converter (TIBC). It uses only one active switch and provides a wider voltage conversion range than other well-known step-down converters. In the paper, the operation of the proposed converter is described. Circuit analysis is performed to derive the voltage gain and key current and voltage equations. The prototype circuit operating with the input voltage of 150 V, the output voltage of 5 V, the load current of 10 A and the switching frequency of 100 kHz is implemented. Experimental results show that the prototype converter exhibits good output voltage regulation and achieves the 30-to-1 voltage step-down operation with a maximum efficiency of 82%. In addition, measurement results confirm that the converter operation is consistent with the theoretical analysis.
Keywords: Advanced DC-DC Converters; Induction Heating and Inverter Technology; Multilevel Inverters and Converters